A tabu search heuristic for solving the multi-depot, multi-vehicle, double request dial-a-ride problem faced by a healthcare organisation. (14th February 2011) - Melachrinoudis, Emanuel; Min, Hokey
In the Center for Addictive Behavior Health and Recovery Services, Inc. (CAB) based in Massachusetts, a dial-a-ride system has been in operation to serve outpatients such as drug and alcohol addicts requesting both delivery and pickup services through telephone calls. As the number of outpatients continues to increase with constrained vehicle capacity and operating budget, CAB copes with the onerous task of minimising the service disruptions and vehicle operating costs. To handle this challenging task, we developed an integer programming model and a tabu search heuristic for solving that model. A series of computational experiments that we made through the real-world problems encountering CAB substantiated the practicality of the proposed model and tabu search heuristic. In addition, the solution quality (accuracy) and computational efficiency of the tabu search heuristic were verified by comparing its test result to those of the branch and bound algorithm.